New Strait Times, 4 May 2009 - Azura Abas (The New Straits Times Press (M) Bhd, 2009)
Testing for the influenza A (H1N1) virus will take only six hours unstead of three weeks once a new test kit arrives from the US Centers for Disease Control and Prevention.